The telesis report - a review essay - Nolan, S (Economic & Social Studies, 1983)
Since 1979, the National Economic and Social Council (NESC) has been carrying out a broad re-examination of the package of government policies used to promote Ireland's industrial development. NESC Report No. 64, A Review of Industrial Policy ?The Telesis report ? is the centre piece of this review and is a study of potentially major importance in that it is the first large-scale attempt to provide a comprehensive assessment of Ireland's industrial structure and industrial policies. The choice of a foreign-based management consultancy group to carry out the study in some ways adds to the significance of the report, given that the authors are free from any ties with domestic institutions and interest groups, and that their analysis cannot be dismissed by applied policy-makers as being "too academic" or "right, in theory but irrelevant in practice".
Keywords: Economics; Sociology